Cross-contamination Risks in Dry Produce Packinghouses: Efficacy of Alcohol-based Sanitizers to Reduce Salmonella and Potential Surrogates on Relevant Surface Materials - Alexandra Nerney; Stuart Reitz; Jovana Kovacevic; Joy Waite-Cusic (Journal of Food Protection)
A 2020 Salmonella outbreak was epidemiologically linked to red onions; however, insufficient cleaning and sanitation in the packinghouse expanded the recall to include all onions handled by the packing house in the preceding 3 months. Our objective was to evaluate the efficacy of dry sanitizers to reduce cross-contamination risk on food contact surfaces (FCSs) found in postharvest packing areas. Transfer of Salmonella and potential surrogates (Escherichia coli, Enterococcus faecium) to and from onions to FCS materials (high-density polypropylene, polyester-nylon conveyor belts, plywood) was quantified. Transfer rates from inoculated onions to FCS were highly variable, but did not differ by surface, averaging −1.19 log %. Transfer rates from contaminated FCS to uninoculated onions averaged 0.2 log %, with 40% (31/81) of onions having no detectable transfer. Onion variety, surface type, and species did not influence the transfer rate (p > 0.05). Commercial sanitizers and alcohol solutions were tested for efficacy of reducing targeted bacteria on FCS. Reductions were quantified after 30 s and after drying (15 min). High alcohol sanitizers (∼60%) achieved a 5-log reduction on HDPE after drying. Lower alcohol (<30%) products were ineffective (<2-log reduction). E. coli and Salmonella were comparable in sensitivity to sanitizers, but E. faecium was more sensitive (p < 0.05). Transfer and sanitizer evaluation was scaled to investigate cross-contamination in postharvest storage bins (plastic and wood). With no sanitation, inoculated plastic bin contact resulted in contamination of 49–71% of onions. Use of ∼60% alcohol solutions reduced contamination to <4% of onions (p < 0.05). Low-alcohol product significantly increased cross-contamination to 86–100% of onions (p < 0.05). These findings highlight the importance of validating sanitizer efficacy to quantify microbial reduction and cross-contamination risk on produce contact surfaces.